Assessment of puberty in children with chronic kidney disease and end-stage renal disease undergoing hemodialysis - Emad E. Ghobrial; Rasha E. Galal; Maha S. Gadass; Yomna M. Shaalan (SpringerOpen, 2022)
Abstract Background Growth and pubertal retardation are one of the most visible comorbidities in children with chronic kidney disease (CKD) and end-stage renal disease (ESRD) under regular hemodialysis. This study evaluated pubertal development in children and adolescents with CKD and ESRD on regular hemodialysis. Methods This study was carried out on 40 children with CKD and 20 with ESRD under regular hemodialysis. All patients and controls were subjected to a thorough clinical examination pubertal assessment. Results There was a statistically significant difference in the breast or testicular stage of the three groups (P < 0.001). Most cases of ESRD were either stages 1 or 2 (50.0%, 45.0%, respectively). The CKD cases were also stages 1 and 2 (35.7%, 52.4%, respectively). The controls were in stages 3 and 4 (44.3 and 29.5%, respectively), which showed normal development for age. There was a statistically significant difference in the pubic hair stage and axillary hair stage of the three groups (P < 0.001). Most cases of ESRD were either stages 1 or 2 (55.0%, 40.0%, respectively). The CKD cases were also between stages 1 and 2 (38.1%, 52.4%, respectively), with a higher level in stage 2. Of the control group, 39.3% was stage 3, and 36.1% was stage 4, with a higher level in stage 3 proving normal development for age. Conclusion Pubertal growth and sexual maturation in children with CKD and ESRD are markedly affected. It is necessary to regularly follow up with children with ESRD for early detection of endocrinal complications.